2017
DOI: 10.18632/oncotarget.16288
|View full text |Cite
|
Sign up to set email alerts
|

Individual isotoxic radiation dose escalation based on V20 and advanced technologies benefits unresectable stage III non-small cell lung cancer patients treated with concurrent chemoradiotherapy: long term follow-up

Abstract: Under the assumption that the highest therapeutic ratio could be achieved by increasing the total tumor dose (TTD) to the limits of normal tissues, the phase I trial was conducted in patients with unresectable stage III non-small cell lung cancer treated with concurrent chemoradiotherapy, to determine the feasibility and effects of individual isotoxic radiation dose escalation based on bilateral lung V20 and advanced technologies. Consecutive eligible patients were assigned to cohorts of eight. V20 of each coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“… 17 The present study recommends 60-66 Gy as the optimal dose. 11 , 17 , 18 In summary, not all patients diagnosed with unresectable stage III NSCLC are suitable for concurrent chemoradiotherapy. All patient factors must be taken into account before decisions are made.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 17 The present study recommends 60-66 Gy as the optimal dose. 11 , 17 , 18 In summary, not all patients diagnosed with unresectable stage III NSCLC are suitable for concurrent chemoradiotherapy. All patient factors must be taken into account before decisions are made.…”
Section: Discussionmentioning
confidence: 99%
“…We did not record parameters such as V20 that may be related to radiation pneumonitis. 18 These factors may have had an impact on the results. Third, different chemotherapy regimens may have different effects on the hemograms, 24 - 26 but more cycles of induction chemotherapy resulted in more hematological toxicities.…”
Section: Discussionmentioning
confidence: 99%
“…8 Many studies still supported the idea that high dose of radiotherapy was necessary. [17][18][19][20] After the report of RTOG0617 study in 2012, Machtay et al conducted a meta-analysis, which included seven prospective randomized concurrent chemoradiotherapy studies about locally advanced NSCLC. The study 21 showed that BED ≥74.67 Gy (conventional fractionated dose 62-64 Gy) was more beneficial to improve the local control and survival, increasing the time-adjusted BED (tBED) of 1 Gy can increase the local control by 3%, and the BED of 1 Gy can increase OS by 4%.…”
Section: Discussionmentioning
confidence: 99%
“…A phase II clinical study by KongFM et al showed that the local control rate was 82% at 2 years and 30% at 5 years because of the high radiotherapy dose (86 Gy/30 day) with adaptive radiotherapy guided by PET/CT 8 . Many studies still supported the idea that high dose of radiotherapy was necessary 17‐20 . After the report of RTOG0617 study in 2012, Machtay et al conducted a meta‐analysis, which included seven prospective randomized concurrent chemoradiotherapy studies about locally advanced NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…28.9 [10] .Uncontrolled local tumors may be a potential source of distant metastasis [13] .Although the RTOG0617 study showed that 60 Gy may be more reasonable than other radiation dose [3] , further analysis of the study showed that the result was affected by many other factors [12] .There is still debate about that increasing the dose of radiation therapy can reduce recurrence and prolong survival. A phase II clinical study by KongFM et al showed that the local control rate was 82% at 2 years and 30% at 5 years because of the high radiation therapy (86Gy/30day) with adaptive radiotherapy guided by PET/CT [4] .Many studies still supported the idea that high dose of radiation therapy was necessary [14][15][16][17] .After the report of RTOG0617 study in 2012, MachtayM et al conducted a meta-analysis, which included 7 prospective randomized concurrent chemoradiotherapy studies about locally advanced NSCLC. The study [18] showed that BED ≥ 74.67 Gy (conventional fractionated dose 62-64Gy) was more beneficial to improve the local control and survival, increasing the tBED of 1 Gy can increase the local control by 3%, and the BED of 1 Gy can increase OS by 4%.After conventional fractionated radiotherapy, dose escalation for local tumor may improve local control and survival [19] .…”
Section: Discussionmentioning
confidence: 99%